The variability in time of the occurrence conditions of debris flow after catastrophic typhoons and earthquakes: a theoretical explanation with experimental tests - tsai, Y.J.; wang, K.C.; chen, Y.S.; shieh, C.L. (Italian journal of engineering geology and environment, 2011)
In Taiwan, large and often catastrophic typhoons and earthquakes are both factors to trigger serious landslides in mountains. The presences of large amounts of sediments due to the landslides increase the occurrence of debris flow. Base on post-event data, the threshold of debris flow occurrence decreases soon after an earthquake indicating a fast recovery. A relationship of debris flow occurrence from eGasHiRa (1997) is applied, which shows fine sediment plays an important role with debris-flow development and occurrence. In this paper, a series mobile-bed experiments were done to access the influence of the concentration change from upstream discharge with fine/ coarse particle. Two variables were recorded in the experiment, which were depth-ratio (sediment layer depth/ total depth), and the sediment discharge. With comparison with theoretical relationship, the result shows the occurrence condition varied with the ratio of fine sediment.